The Kinds of Illocutionary Act by Yusuf Hamka in Youtube Channel Deddy Corbuzier Podcast - Nasution, Muhammad Muslim; Afria, Rengki; Izar, Julisah (Fakultas Ilmu Budaya, Universitas Jambi, 2022)
Abstract: This study aimed to describe the types of illocutionary speech acts found in Yusuf Hamka's statements on Dady Corbuzier's YouTube channel podcast. This research used descriptive research with a qualitative approach. The data obtained in this study were Yusuf Hamka's speech which was accessed on Deddy Corbuizer's YouTube podcast channel. Data collection techniques in this study used observing and note-taking techniques, while the data collection techniques used were data reduction and data concluding. The research results obtained are, the five types of illocutionary speech acts 1). Assertive, 2). Directive, 3). expressive 4). commissive. 5) Declarative is found in Yusuf Hamka's statement on Deddy's Corbuzier podcast. The conclusion of this study is that all utterances will contain illocutionary speech acts if the said words are included in the classification of the five types of speech acts that exist in illocutionary acts. Keywords: Speech acts; illocutionary acts; youtube; podcast